Robust estimation of voltage parameters via a sliding mode observer. (May 2019) - Tian, Zhen; Yuan, Jingqi
Abstract: Grid voltage parameters are essential for the real-time control and protection in power systems. Current approaches mainly focus on the phase-locked loop methods, but which are slow and sensitive to voltage variations and disturbances. In this paper, the estimation of grid voltage parameters is recast as an observer design problem. A second-order sliding mode observer (SMO) is designed to estimate the grid voltage parameters based on the exosystem model. Moreover, the asymptotic stability of the closed-loop SMO is proved. Simulation and experimental results are presented to illustrate the effectiveness of the proposed approach, which achieves fast response and accurate estimation Highlights: An exosystem model is introduced to represent the sinusoidal voltage. A lowest-order sliding mode observer is designed to estimate grid voltage parameters. The proposed approach achieves fast response and strong robustness with global stability. The effectiveness is verified by both simulation and experimental results.